VISIT-TO-VISIT BLOOD PRESSURE VARIABILITY IN RURAL MALES WITH ARTERIAL HYPERTENSION: THE POSSIBILITIES OF MODIFYING IN REAL CLINICAL SETTINGS - T.I. Nimtsovych; К.О. Mikhaliev; A.M. Kravchenko; V.G. Gurianov; T.Ya. Chursina; O.Yu. Mishcheniuk; S.S. Stanislavska (Клінічна та профілактична медицина, 2020)
Purpose: to establish the possibilities of modifying blood pressure visit-to-visit variability (VVV) in rural males with arterial hypertension (HTN) by the use of antihypertensive therapy (AHT), considering also the correction of dyslipidemia and certain lifestyle aspects, as well as the changes in compliance with pharmacotherapy (CP).